2019
DOI: 10.1016/j.epsl.2019.03.030
|View full text |Cite|
|
Sign up to set email alerts
|

Lateral variation in crustal structure along the Lesser Antilles arc from petrology of crustal xenoliths and seismic receiver functions

Abstract: 13We reconstruct crustal structure along the Lesser Antilles island arc using an inversion 14 approach combining constraints from petrology of magmatic crustal xenoliths and seismic 15 receiver functions. Xenoliths show considerable island-to-island variation in xenolith 16 petrology from plagioclase-free ultramafic lithologies to gabbros and gabbronorites with 17 variable proportions of amphibole, indicative of changing magma differentiation depths. 18Xenoliths represent predominantly cumulate compositions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 57 publications
8
62
2
Order By: Relevance
“…These results are confirmed and extended to the whole active arc by a recent reconstruction of the crustal structure using an inversion approach combining petrology of magmatic crustal xenoliths and seismic receiver functions ( Fig. 9a; Melekhova et al 2019). Both studies agree that the mid-crustal discontinuity beneath Dominica is located at~13-16 km, i.e.…”
Section: Structure Of the Magmatic System Beneath Dominicasupporting
confidence: 83%
See 2 more Smart Citations
“…These results are confirmed and extended to the whole active arc by a recent reconstruction of the crustal structure using an inversion approach combining petrology of magmatic crustal xenoliths and seismic receiver functions ( Fig. 9a; Melekhova et al 2019). Both studies agree that the mid-crustal discontinuity beneath Dominica is located at~13-16 km, i.e.…”
Section: Structure Of the Magmatic System Beneath Dominicasupporting
confidence: 83%
“…At the Antilles arc, one explanation for the voluminous storage region in Dominica being deeper than the ones on the neighbouring volcanic islands could be an along-arc fluctuation of the crustal structure. Indeed, previous seismic refraction studies suggested significant differences in the crust thickness, with the thickest one being under Dominica (up to 37 km; Melekhova et al 2019) and in the depth of the middlelower crust interface, with variations from 2 to 20 km (Boynton et al 1979;Macdonald et al 2000;Melekhova et al 2019). However, this mid-crustal discontinuity could be at similar depth below Martinique, Montserrat and Dominica ( Fig.…”
Section: Comparison With Magma Storage Conditions On the Neighbouringmentioning
confidence: 81%
See 1 more Smart Citation
“…Balcone‐Boissard et al (2018) and Solaro et al (2019) determined that the magma(s) feeding the ignimbrite eruptions were stored at a depth of approximately 16 km beneath Dominica. Using crustal density models of Kopp et al (2011) and Melekhova et al (2019) to the North of Dominica, Solaro et al (2019) deduced that these depths correspond to the boundary between the lower and middle crusts. According to the same crustal models, our results suggest storage of the magmas that fueled the plinian eruptions at the limit between the middle and upper crusts, or within the upper crust.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies thus suggest that a magma ponding zone is commonly developed at a depth of approximately 5 to 8 km beneath the islands of the Lesser Antilles arc, corresponding to the limit between upper and middle crusts, according to the crust model proposed by Melekhova et al (2019). The wide range of storage depths beneath Dominica (Balcone‐Boissard et al, 2018; Solaro et al, 2019; this study), Martinique (Annen et al, 2008; Martel et al, 1998; Pichavant et al, 2002), Guadeloupe (Pichavant et al, 2018), and Montserrat (Devine et al, 2003; Edmonds et al, 2016) is in good agreement with a transcrustal magma system (Cashman et al, 2017) and allows to suspect such plumbing systems also beneath other, less‐studied islands of the Lesser Antilles arc.…”
Section: Discussionmentioning
confidence: 99%